Variation in the age at natural menopause among Polish women in relation to their reproductive histories - Kaczmarek, Maria (Menopause Review/Przegląd Menopauzalny, 2008)
Objective: This study aims to provide an assessment of the reproductive history variables hypothesized as covariates of the age at natural menopause in a population-based sample of Polish women. Materials and methods: The study sample consisted of 7183 women, aged between 35 and 65 years, from all social strata of the non-clinical population. They participated in the WOMID project, carried out across Poland between 2000 and 2004. The demographic, social, and reproductive history aspects of the menopause-specific questionnaire were examined. Event history analysis was used to identify events of the reproductive history associated with the age at natural menopause. Non-parametric Kaplan-Meier cumulative survivorship estimates were used to assess the age at natural menopause. Results: The findings of the multiple Cox models enabled us to identify variables which were associated with the age at natural menopause. Early menarche, short menstrual cycle length, and low level of education were associated with menopause at younger age (p<0.01). Use of oral contraceptives and parity were associated with menopause at older age (p<0.01). The following variables appeared not to be associated with age at natural menopause: marital status, residence place, intergenetic interval, and breast feeding. Conclusion: The study revealed considerable intra-population variation in the age at natural menopause and the contribution of reproductive-history factors to this variation.